The Role of Image Maintenance and Image Creation Factors in Indonesia's Coal Industry by PT. Asiatic Universal Indonesia from the Perspective of Job Feasibility Analysis and the Impact of Economic Growth in East Kalimantan Province - Fetrie J.L Maramis; Mochammad Kresna Noer (Riviera Publishing, 2026)
This study is grounded in the global and national challenges faced by the coal industry, particularly the tension between its economic contribution and the increasing environmental and social pressures. In Indonesia, coal remains a key driver of economic growth and employment, especially in resource-rich regions such as East Kalimantan. However, the industry is often associated with negative perceptions related to environmental degradation, which threatens its social legitimacy. The purpose of this study is to analyze the role of image maintenance and image creation strategies implemented by PT Asiatic Universal Indonesia and to examine their impact on job feasibility and regional economic growth. This research employs a descriptive qualitative method, using in-depth interviews, document analysis, and limited observation to obtain comprehensive insights from various stakeholders, including company management, employees, local communities, and government representatives. The findings indicate that image maintenance strategies, such as regulatory compliance, CSR programs, and transparent communication, play a significant role in maintaining public trust and securing the social license to operate. Meanwhile, image creation strategies focusing on economic contributions, job creation, and technological innovation help reshape public perceptions of the coal industry. These strategies collectively contribute to improving job stability, enhancing workforce quality, and increasing employee satisfaction. In conclusion, image management in the coal industry is not merely a communication tool but a strategic mechanism that directly affects employment feasibility and regional economic growth. Effective integration of image maintenance and image creation can ensure business sustainability, strengthen stakeholder relationships, and support long-term economic development.